2016
DOI: 10.1002/oby.21697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of three human adipocyte size measurement methods and their relevance for cardiometabolic risk

Abstract: Objective: To determine whether adipocyte diameters from three measurement methods are similarly associated with adiposity measurements and cardiometabolic variables. Methods: Surgical samples of omental and abdominal subcutaneous adipose tissue were obtained in a sample of 60 women (age 35-59 years; body mass index 20.3-41.1 kg/m 2 ). Median adipocyte diameter of the main cell population was determined by collagenase digestion, osmium tetroxide fixation, and histological analysis. Adiposity and cardiometaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 34 publications
7
58
0
Order By: Relevance
“…Measurement of adipocyte size or enumeration of ATM in relation to the number of adipocytes has been done in previous studies. However, adipocyte size can change with the processing of tissue into histologic sections, resulting in a questionable accuracy of those measurements (Laforest et al, 2017). Due to the inherent inconsistencies in adipocyte size due to fixation, we chose to enumerate the number of cells in an equivalent number of fields across all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of adipocyte size or enumeration of ATM in relation to the number of adipocytes has been done in previous studies. However, adipocyte size can change with the processing of tissue into histologic sections, resulting in a questionable accuracy of those measurements (Laforest et al, 2017). Due to the inherent inconsistencies in adipocyte size due to fixation, we chose to enumerate the number of cells in an equivalent number of fields across all cases.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, we find that whilst adipocyte area estimates vary substantially dependent on the method used for quantification, the correlation of adipocyte size and obesity is robust to these differences. 26 Our Adipocyte U-net required less than 6 minutes to predict adipocyte surface area across the ~10,000 images included in fatDIVA and MOBB. In comparison, Adiposoft took~3.5 hours.…”
Section: Figure 2 | Comparison Of Adipocyte U-net-estimated Adipocytementioning
confidence: 99%
“…Laforest et al (5), like researchers before them (1), found that the size of osmium-fixed adipocytes was larger (25%), most likely due to the swelling of the fixed lipid droplet (1). Does it matter that "actual" adipocyte size is likely overestimated after osmium fixation if it better predicts metabolic risk?…”
mentioning
confidence: 92%
“…They found fairly good correlations among the three commonly used cell sizing methods (collagenase‐isolated cells, histological tissue sections, and electronic (Multisizer™) sizing of osmium‐fixed adipocytes) yet intriguingly report that the median adipocyte size measured by electronic counting of osmium‐fixed cells best correlated with measures of glucose homeostasis, lipid profiles, and circulating adipokine levels. Beyond the advantages/disadvantages of each method , these new findings bring up several issues that merit wider discussion.…”
mentioning
confidence: 99%
See 1 more Smart Citation